Do Sheep Dream of Electric Ruins? Encounters with Transatlantic Wireless Landscapes - Matt Parker (VIEW Journal of European Television History and Culture)
This article examines the Derrigimlagh bog in Ireland as a site of infrastructural ruination and media archaeology, focusing on the remnants of the Marconi transatlantic wireless station and the broader implications of technological obsolescence. Through an interdisciplinary approach combining environmental humanities, media archaeology, and speculative documentary practices, the study considers how the bog serves as both a repository of past electromagnetic infrastructures and a terrain for imagining future cycles of extraction and decay. The presence of sheep grazing among the ruins is analysed as a material and symbolic intervention, reframing nonhuman agency within the entanglement of media, landscape, and industrial afterlives.